Equilibrium shift, poisoning prevention, and selectivity enhancement in catalysis via dehydration of polymeric membranes - Hyeon, Myeong Hun; Park, Hae Gu; Lee, Jongmyeong; Kong, Chang In; Kim, Eun Young; Kim, Jong Hak; Moon, Su Young; Kim, Seok Ki (Nature Communications, 2023)
Generation of water as a byproduct in chemical reactions is often detrimental because it lowers the yield of the target product. Although several water removal methods, using absorbents, inorganic membranes, and additional dehydration reactions, have been proposed, there is an increasing demand for a stable and simple system that can selectively remove water over a wide range of reaction temperatures. Herein we report a thermally rearranged polybenzoxazole hollow fiber membrane with good water permselectivity and stability at reaction temperatures of up to 400 °C. Common reaction engineering challenges, such as those due to equilibrium limits, catalyst deactivation, and water-based side reactions, have been addressed using this membrane in a reactor.